The Effect of Prodigiosin Extracted from Serratia marcescens on DNA Fragmentation of Human Peripheral Blood Lymphocytes Cells - K. Abid, Huayda (Iraqi Journal of Science, 2023)
Prodigiosin, is a natural red pigment produced by various bacteria that firstlycharacterized from Serratia marcescens. It is an alkaloid secondary metabolite witha unique tripyrrol structure.This pigment is a promising drug owing to its reportedcharacteristics of having antifungal, immunosuppressive and anti-cancer activity. Inthis study prodigiosin was produced by Serratia marcescens., which was isolatedfrom soil identified and characterized by morphology, Gram’s staining, biochemicaland carbohydrate fermentation tested and confirmed by the API 20E test.From these samples, six isolates of Serratia marcescens( 24) % were obtained outof 25 soil samples. Ability of these isolates in prodigiosin production was examinedto select the efficient isolate in prodigiosin production.Results showed that all ofthese isolates are prodigiosin producers, and among them one isolate was the mostefficient in prodigiosin production.The apoptotic effect of the pigment was assessed in blood lymphocytes cells byDNA fragmentation analysis assay collected from anticoagulated human blood ,prodigiosin at all concentrations were significantly increased the percentage offragmented DNA of peripheral blood Lymphocyte cells compared to control. Thisstudy reveals that Prodigiosin has possessed apoptotic property.